2011
DOI: 10.1371/journal.pone.0025610
|View full text |Cite
|
Sign up to set email alerts
|

Impaired CD4 T Cell Memory Response to Streptococcus pneumoniae Precedes CD4 T Cell Depletion in HIV-Infected Malawian Adults

Abstract: ObjectiveInvasive pneumococcal disease (IPD) is a leading cause of morbidity and mortality in HIV-infected African adults. CD4 T cell depletion may partially explain this high disease burden but those with relatively preserved T cell numbers are still at increased risk of IPD. This study evaluated the extent of pneumococcal-specific T cell memory dysfunction in asymptomatic HIV infection early on in the evolution of the disease.MethodsPeripheral blood mononuclear cells were isolated from asymptomatic HIV-infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
46
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 47 publications
8
46
1
Order By: Relevance
“…Our findings are consistent with previous reports that despite sustained HIV-RNA viral suppression and restoration of circulating CD4+ T-cell numbers to levels above 450 cells/μl, specific immune responses among ART-treated adults remain dependent upon the pre-ART CD4 counts [15]. Functional defects in pneumococcal-specific T-cell memory and regulation were previously reported during the course of HIV disease [16]. Our study participants initiated ART at advanced stages of HIV disease which makes complete restoration of their immune responses very difficult.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are consistent with previous reports that despite sustained HIV-RNA viral suppression and restoration of circulating CD4+ T-cell numbers to levels above 450 cells/μl, specific immune responses among ART-treated adults remain dependent upon the pre-ART CD4 counts [15]. Functional defects in pneumococcal-specific T-cell memory and regulation were previously reported during the course of HIV disease [16]. Our study participants initiated ART at advanced stages of HIV disease which makes complete restoration of their immune responses very difficult.…”
Section: Discussionsupporting
confidence: 92%
“…A major strength was using two complimentary methods for determining antigen-specific CD4 T-cell immune responses to common antigens in this setting [16,26,27]. Many studies have looked at proliferation and discontinuation of prophylaxis without analysis of cytokine production profiles [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, despite few studies describing higher levels of isotype switched B cells in treated patients compared to naive [27] and differentiate from HIV negative individuals [28], our study confirmed more recent authors [29], underlining the need for further investigation on this specific memory subset.…”
Section: Discussionsupporting
confidence: 86%
“…We have previously shown that in asymptomatic HIV-infected individuals (WHO Stage I), the proportion of naive T cells is comparable to healthy HIV-negative persons but memory cells are proportionally decreased [11]. We now show no change in the proportion of naive CD4 + T cells (CCR7 + CD45RA + )[21], [22] between 0 and 6 months ART-mediated immune reconstitution but that this subset had further increased by 12 months ( Figure 1B , p = 0.0001), to levels even higher to those seen in HIV–uninfected individuals (median 35.73% vs 19.36%, p = 0.0234).…”
Section: Resultsmentioning
confidence: 99%